2020
DOI: 10.1037/sah0000210
|View full text |Cite
|
Sign up to set email alerts
|

Visible and concealable stigmatized identities and mental health: Experiences of racial discrimination and anticipated stigma.

Abstract: Experiencing and anticipating discrimination because one possesses a visible (e.g., race) or concealable (e.g., mental illness) stigmatized identity has been related to increased psychological distress. However, little research has examined whether experiencing and anticipating discrimination related to possessing both a visible and concealable stigmatized identity (e.g., a racial/ethnic minority with a history of mental illness) impacts mental health. In the current study, we test 2 hypotheses. In the first, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…Fear was ubiquitous including of being perceived as “weak,” “crazy,” or “dangerous” (Carpenter‐Song et al., 2014; Haynes et al., 2017; Johnson et al., 2009), and of the “double” discrimination of being Black and having a mental illness, particularly among women (Alang, 2019). In a quantitative study, experiencing stigma for being Black or Latinx led to more anticipated stigma for having a mental illness (Quinn et al., 2019). Black adolescents expressed shame about needing medications (Kranke et al., 2012) and using mental health services, although the latter was moderated by social support (Lindsey et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Fear was ubiquitous including of being perceived as “weak,” “crazy,” or “dangerous” (Carpenter‐Song et al., 2014; Haynes et al., 2017; Johnson et al., 2009), and of the “double” discrimination of being Black and having a mental illness, particularly among women (Alang, 2019). In a quantitative study, experiencing stigma for being Black or Latinx led to more anticipated stigma for having a mental illness (Quinn et al., 2019). Black adolescents expressed shame about needing medications (Kranke et al., 2012) and using mental health services, although the latter was moderated by social support (Lindsey et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…If an individual expects the other person to respond poorly to an admission, confiding in them should be less likely. For instance, prior episodes of devaluation will prompt expectancies of future devaluation (e.g., Mendoza-Denton et al, 2002; Quinn et al, 2019). Accordingly, prior experiences of being stigmatized will likely inform whether a secret is kept entirely to oneself or selectively confided.…”
Section: J Revealmentioning
confidence: 99%
“…Nevertheless, our results are consistent with other recent investigations using US and UK samples ( Bray et al, 2021 ; Czeisler et al, 2020 ; Fitzpatrick et al, 2020 ; Proto and Quintana-Domeque, 2021 ) which have documented disparities in psychological distress and suicidality among Black and other racial/ethnic groups compared to their White peers. Numerous studies have demonstrated that factors such as overt racial discrimination and racial microaggressions ( Paradies et al, 2015 ; Quinn et al, 2020 ; Rosario-Williams et al, 2022 ; Shi et al, 2022 ), socioeconomic inequalities ( Lo and Cheng, 2018 ; Williams, 2018 ), and medical mistrust ( Hammond, 2010 ; Powell et al, 2019 ) have contributed significantly to greater risks of suicidality, particularly among racial/ethnic minority groups in the United States. The substantially greater relative risk of suicidality among racial/ethnic minorities highlights the critical need of culturally responsive suicide prevention services for this population, particularly given that disparities in mental health by race/ethnicity in the United States have been demonstrated in the emerging COVID-19 literature.…”
Section: Discussionmentioning
confidence: 99%